Developing writing competencies : a case study of educators' experiences with a READ Educational Trust training programme in primary schools - Fraser, William John (University of Pretoria, 2013)
Thesis (PhD (Assessment and Quality Assurance in Education and Training))--University of Pretoria, 2008.